Abrasive wear resistance of bainite - Брыков, М.Н. (Problems of Tribology, 2015)
Brykov M.N. Abrasive wear resistance of bainite The results of investigation on abrasive wear resistance of steels containing bainite are presented. Steels of two chemical compositions are tested: both for ferrite-cementite bainite and ferrite-austenite bainite. It is shown, that if bainite quantity in the structure of steel increases than wear resistance decreases.